Influence of operational variables in a hydrodynamic bearing on the generation of acoustic emission - Mirhadizadeh, S. A.; Moncholi, E. P.; Mba, David (Elsevier Science B.V., Amsterdam., 2010)
Detecting mechanical faults of rotating machines particularly in hydrodynamic bearings has been recognised as important for preventing sudden shut downs. This technical note presents an experimental investigation that is aimed at understanding the influence of operational variables (speed, load, etc) on generation of acoustic emission in a hydrodynamic bearing. It is concluded that the power losses of the bearing are directly correlated with acoustic emission levels.
Keywords: Acoustic emission; Hydrodynamic; Bearing; Condition monitoring